The Effect of Applying Collaborative Strategic Reading on Grade VIII Students’ Achievement in Reading Comprehension - Rosniati Lubis; Meisuri Meisuri (GENRE JOURNAL : Journal of Applied Linguistics of FBS Unimed, 2013)
The objective of this study was to investigate whether Collaborative Strategic Reading significantly affected on students’ reading comprehension. This study was an experimental design. The population of this study was grade VIII students’ of SMP IT Nur Ihsan Medan with the total number 34 students, which was taken as the sample by using total sampling. The students were divided into two groups, namely experimental and control group. The Experimental group was taught by using Collaborative Strategic Reading while the control group was taught without using Collaborative Strategic Reading. The instrument of collecting data was multiple choice test. Content validity was applied in this research. To obtain the reliability of the test, the researcher used the Kuder Richardson (KR-21). The result of the research showed that the reliability of the test was 0.76, it means that the reliability of the test is high. The data were analyzed by using t-test formula. The result of the analysis revealed that t-test is higher than t-table (3.21 > 2.04) at the level significance 0.05 with the degree of freedom (df) = N-2 = 32. It means that there is a significant effect of applying Collaborative Strategic Reading on the students’ achievement in reading comprehension.Key words: Reading Comprehension, Collaborative Strategic Reading, and Students’ Achievement